Pharmacokinetics, pharmacodynamics, and safety of ciprofol emulsion in Chinese subjects with normal or impaired renal function - Tao, Jun; Liu, Shuaibing; Zhao, Ying Ying; Qi, Lei; Yan, Pangke; Wu, Nan; Liu, Xiao; Liu, Dongwei; Tian, Xin (Frontiers in Pharmacology, 2023)
Ciprofol, a novel sedative-hypnotic drug, has been approved for its use in inducing and maintaining general anesthesia, as well as for providing sedation. In this Phase I, singlecenter, parallel, controlled, open-label clinical trial, our objective was to analyze the pharmacokinetics (PK), pharmacodynamics (PD), and safety of ciprofol emulsion in 24 participants with mild and moderate renal impairment (n = 8 per group), and matched healthy participants (n = 8). An initial loading dose of ciprofol was administered at 0.4 mg/kg for 1 min, followed by a maintenance infusion at a rate of 0.4 mg/kg/h for 30 min. We collected plasma and urine samples from the participants to assess the PK of ciprofol and its metabolite M4. The evaluation of PD involved using a modified observer's alertness/sedation scale (MOAA/S) in combination with bispectral index (BIS) monitoring. Safety assessments were conducted throughout the trial process. The plasma concentration-time curve of ciprofol in participants with renal impairment was similar to that in participants with normal kidney function. The area under the curve (AUC) and maximum concentration (Cmax) of total and unbound ciprofol in plasma for participants with renal impairment were only slightly higher (0.7-to 1.2-fold) than those in participants with normal renal function. In contrast, for the metabolite M4, AUC values were 1.3-and 2.1-fold greater in participants with mild and moderate renal impairment, respectively, compared to healthy controls. However, renal impairment had no significant impact on the PD parameters. The study found that ciprofol was welltolerated, with all adverse events AEs reported being mild or moderate in severity.Based on these findings, we can conclude that no dosage adjustment of ciprofol is necessary for patients with mild-to-moderate renal impairment who receive the injection.